Neuromodulation as a cognitive enhancement strategy in healthy older adults: promises and pitfalls - Martins, Ana R. S. (2016)
Increases in life expectancy have been followed by an upsurge of age-associated cognitive decline. Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have risen as promising approaches to prevent or delay such cognitive decline. However, consensus has not yet been reached about their efficacy in improving cognitive functioning in healthy older adults. Here we review the effects of TMS and tDCS on cognitive abilities in healthy older adults. Despite considerable variability in the targeted cognitive domains, design features and outcomes, the results generally show an enhancement or uniform benefit across studies. Most studies employed tDCS, suggesting that this technique is particularly well-suited for cognitive enhancement. Further work is required to determine the viability of these techniques as tools for long-term cognitive improvement. Importantly, the combination of TMS/tDCS with other cognitive enhancement strategies may be a promising strategy to alleviate the cognitive decline associated with the healthy aging process.